2018
DOI: 10.1080/19336950.2018.1457897
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-mediated calcium channel regulation in synaptic suppression in L. stagnalis interneurons

Abstract: D2 dopamine receptor-mediated suppression of synaptic transmission from interneurons plays a key role in neurobiological functions across species, ranging from respiration to memory formation. In this study, we investigated the mechanisms of D2 receptor-dependent suppression using soma-soma synapse between respiratory interneuron VD4 and LPeD1 in the mollusk Lymnaea stagnalis (L. stagnalis). We studied the effects of dopamine on voltage-dependent Ca2+ current and synaptic vesicle release from the VD4. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…Likewise, dopamine, acting at G protein-coupled receptors, produced only voltage-independent inhibition of Ca 2ϩ channels in Aplysia neurons (37), despite its ability to produce voltage-dependent inhibition of I Ca in vertebrates. More recently, however, evidence has emerged that dopamine mediates inhibition at a Lymnaea synapse, at least partially via voltage-dependent inhibition of I Ca (27). Our findings here that invertebrate VGCCs are indeed capable of undergoing G protein-mediated voltagedependent inhibition provide further compelling evidence that this type of neuronal inhibition is conserved between vertebrates and at least some invertebrates.…”
Section: Invertebrate Voltage-gated Ca 2؉ Channels Are Capable Of Undsupporting
confidence: 60%
See 1 more Smart Citation
“…Likewise, dopamine, acting at G protein-coupled receptors, produced only voltage-independent inhibition of Ca 2ϩ channels in Aplysia neurons (37), despite its ability to produce voltage-dependent inhibition of I Ca in vertebrates. More recently, however, evidence has emerged that dopamine mediates inhibition at a Lymnaea synapse, at least partially via voltage-dependent inhibition of I Ca (27). Our findings here that invertebrate VGCCs are indeed capable of undergoing G protein-mediated voltagedependent inhibition provide further compelling evidence that this type of neuronal inhibition is conserved between vertebrates and at least some invertebrates.…”
Section: Invertebrate Voltage-gated Ca 2؉ Channels Are Capable Of Undsupporting
confidence: 60%
“…The slowing of activation kinetics and the depolarizing shift in the voltage dependence of channel activation (with no effect on channel inactivation) produced by HX531 are both characteristic of the voltage-dependent inhibition of VGCCs in vertebrate neurons. Voltage-dependent inhibition can be relieved by a large depolarizing prepulse, known to cause the release of inhibitory G␤␥ proteins from the channel (23)(24)(25)(26)(27). To determine whether HX531 produced voltage-dependent inhibition in VF neurons, the cells were treated overnight with either 1 M or 500 nM HX531 or the equivalent concentration of DMSO (0.01%).…”
Section: Hx531 and Le540 Produce Voltage-dependent Inhibition Of Vgccsmentioning
confidence: 99%
“…Finally, for the first time, we systematically identified transcripts that putatively encode 43 subtypes of Na + , K + , Ca 2+ , Cland cation ion channels and ionotropic neurotransmitter receptors (Figure 8-14, Table S15-23), greatly expanding our understanding of the molecular determinants of neural excitability and transmission in the L. stagnalis CNS. As the L. stagnalis CNS has been widely employed to study ion channels and/or ionotropic neurotransmitter receptors (Spafford, Chen, et al 2003;Lu and Feng 2011;Dawson et al 2014;Dong, Lee, et al 2018), we examined the protein sequence similarity of each identified L. stagnalis channel/receptor transcripts with its homolog in mouse, X. tropicalis, zebrafish, fruit fly and C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for the rst time, we systematically identi ed transcripts that putatively encode 43 subtypes of Na + , K + , Ca 2+ , Cl -, cation, and TRP ion channels and ionotropic neurotransmitter receptors (Figure 8-14, Table S15-23), greatly expanding our understanding of the molecular determinants of neural excitability and transmission in the L. stagnalis CNS. As the L. stagnalis CNS has been widely employed to study ion channels and/or ionotropic neurotransmitter receptors [38,[75][76][77], we examined the protein sequence similarity of each identi ed L. stagnalis channel/receptor transcripts with its homolog in M. musculus, X. tropicalis, D. rerio, D. melanogaster and C. elegans.…”
Section: Discussionmentioning
confidence: 99%